El museo+UCR : una realidad en concreto. 5 años de celebración - Arias Quirós, Ana Cecilia
In 2000, the profile of the Museum of the University of Costa Rica (museo+UCR) began to be defined, and from the Research Center on Latin American Identity and Culture (CIICLA), the Institutional Committee of Collections and the support of university authorities, it was gradually planning, structuring and underpinning its foundations. The long university dream of having a museum was becoming more accurate and closer. Thus, on June 24, 2010, the University Council approved the creation of the museo+UCR. Therefore, in 2015, it celebrated its fifth anniversary of being officially founded. The realization of this has involved an ongoing process of reflection and work with the different collections of the University. In this way, it has been conceptualizing the museum that is required; moreover, it has shown the need for a university museum. Therefore, it has reached the point where it is necessary to have a physical space to place it. Given this, it has outlined a first museographical exercise to see the scope of an intervention to the Faculty of Engineering building complex; this is a patrimonial building destined to house the museo+UCR.